2021
DOI: 10.3390/antibiotics10101227
|View full text |Cite
|
Sign up to set email alerts
|

Is Penicillin Allergy a Risk Factor for Early Dental Implant Failure? A Systematic Review

Abstract: The prescription of preventive antibiotics in dental implant treatments reduces the incidence of early failures. This study has focused mainly on the influence of amoxicillin, which is contraindicated in penicillin-allergic patients. The present systematic review aimed to determine whether penicillin-allergic patients have a higher risk of implant failure compared to non-allergic patients. An electronic search was performed on Medline and Web of Science using the following MeSH terms: (penicillin allergy OR cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Clindamycin is frequently prescribed for penicillinallergic patients as an alternative to oral surgery; however, researchers have recently reported on the lack of highquality clinical evidence for its use in oral implant surgery [28,36,[48][49][50]. Clindamycin is a broad-spectrum antibiotic with activity against aerobic, anaerobic, and β-lactamaseproducing pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clindamycin is frequently prescribed for penicillinallergic patients as an alternative to oral surgery; however, researchers have recently reported on the lack of highquality clinical evidence for its use in oral implant surgery [28,36,[48][49][50]. Clindamycin is a broad-spectrum antibiotic with activity against aerobic, anaerobic, and β-lactamaseproducing pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Clindamycin has appeared as one of the choices for oral implant surgery according to multiple surveys performed in the last few years among oral care professionals [26,[30][31][32][33][34][35][36]. In a survey performed in Spain, 58% of the respondents selected clindamycin as the alternative in cases of an allergy to amoxicillin [36].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are only recommendations based on evidence regarding the placement of unitary implants in ordinary conditions [ 23 ] and bone regeneration with the placement of implants in one or two phases [ 21 ]. In both procedures, the recommended guideline is 2 or 3 g of amoxicillin, one hour before the intervention [ 21 , 23 ] and, in allergic patients, 500 mg of azithromycin one hour before surgery [ 24 ], which would be equivalent to what is recommended to prevent OPIs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is only clear scientific proof on the recommended PA dose in the clinical situation mentioned above [ 23 ] and in bone augmentation with the implant placement done in one or two phases [ 21 ], that is, 2–3 g of amoxicillin an hour before the intervention [ 21 , 23 ], while in allergic patients, 500 mg of azithromycin, 1 h before surgery, has recently been suggested. [ 24 ]. Regarding the remaining clinical situations, the type of antibiotic prescribed and its posology is up to the professional, who in many cases tends to over-prescribe them.…”
Section: Introductionmentioning
confidence: 99%
“…These authors explained these findings with an increased risk of infection in allergic patients [ 28 , 43 ], however, no specific diagnostic test was performed before inclusion in the studies, i.e., patients self-reported to be allergic. In clinical practice, 10–20% of patients report an allergy or reaction to penicillins, however, these are rarely hypersensitivity or immunoglobulin E-mediated reactions [ 44 , 45 , 46 ]. Furthermore, studies have shown that 80–99% of these patients may no longer be considered allergic after testing [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%